Efeitos das dispersões aérea e submersa sobre a entomofauna aquática em um lago raso de planície de inundação Neotropical. - García Ríos, Raúl Fernando (2019)
Dispersion is the mobility factor that determines the presence of organisms in the environment and is a key process that models the local and regional diversity patterns of biological communities. The objective of this work was to evaluate the effect of aerial and submerged dispersions on the aquatic entomofauna in a shallow lake of the high Paraná River floodplain, Brazil. Both the aerial and submerged parts of the floating aquatic macrophyte Eichhornia crassipes were isolated in order to test the hypothesis that: i) the submerged dispersion has a greater contribution in the aquatic insect community structure compared to the aerial dispersion, and ii) the dispersion submersed promotes greater heterogeneity in the composition of the community. Compared with aerial dispersion, the submerged dispersion did not present higher values of taxa richness, organism’s density, Shannon diversity index and equitability. However, in relation to the taxonomic composition, the submerged dispersion promoted high values of community heterogeneity compared to aerial dispersion. The results show that the submerged dispersion promotes the elevation of beta diversity, at least in the local scale studied, spatially structuring the aquatic entomofauna.